The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

EDWARDS, ANNA HARRIETTE - Yorke, Lois K. (Dictionnaire biographique du Canada, 1998)

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

To Indulge their Carnal Appetites: Prostitution in Early Nineteenth-Century Montreal, 1810-1842 - Poutanen, Mary Anne (Université de Montréal, 1997)
Keywords: Police; Prostitution; Tribunaux

Les rapports médecins-infirmières et l'implication de la Métropolitaine dans la lutte contre la mortalité infantile, 1909-53 - Baillargeon, Denyse (Canadian Historical Review, 1996)
Number: 1
Keywords: Assurance; Enfants; Infirmières; La Métropolitaine; Mortalité; Médecine

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Familles ouvrières à Montréal. Âge, genre et survie quotidienne pendant la phase d’industrialisation - Bradbury, Bettina (Boréal, 1995)
Keywords: Alimentation; Famille; Logement; Vêtements

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
issued: 1994-21-00
Keywords: Famille; Femmes

BARRY, ROBERTINE, Françoise - Carrier, Anne (Dictionnaire biographique du Canada, 1994)

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

Le leadership féminin dans les associations privées de charité protestantes au XIXe siècle à Montréal - Harvey, Janice (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Protestants

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger; Jacques

L'histoire des femmes au Québec depuis quatre siècles - Collectif Clio (Le Jour, 1992)
Keywords: Femmes

Les femmes et le vote au Bas-Canada de 1792 à 1849 - Picard, Nathalie (Université de Montréal, 1992)
Keywords: Femmes; Élections

Domaine et tours du fort des messieurs de Saint-Sulpice - Casavant, Germain (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Autochtones; Patrimoine; Sulpiciens

Domaine des soeurs grises de Montréal - Gauthier, Raymonde (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Femmes; Patrimoine; Soeurs Grises

Les vocations féminines de la région montréalaise au XIXe siècle - Payette, Céline (Université du Québec à Montréal, 1991)
Keywords: Communautés religieuses; Femmes

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Quebec Women: a History - Collectif Clio (Women's Press, 1987)
Translators: _:n14097
Keywords: Femmes

Taking the Veil: An Alternative to Marriage, Motherhood, and Spinsterhood in Quebec, 1840-1920 - Danylewycz, Marta (McClelland and Stewart, 1987)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Les communautés religieuses masculines de 1836 à 1920 - Laperrière, Guy (L'Église de Montréal, aperçus d'hier et d'aujourd'hui, 1836-1986, 1986)
Keywords: Communautés religieuses

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Number: 33
Keywords: Famille; Femmes; Travail

Teachers, Gender, and Bureaucratizing School Systems in Nineteenth Century Montreal and Toronto - Danylewycz, Marta; Prentice, Alison Leeds (History of Education Quarterly, 1984)
issued: 1984-21-00
Keywords: Enseignants; Femmes

The Neglected Majority: The Changing Role of Women in Nineteen Century Montreal - Cross, D. Suzanne (The Social Development of Canada - Readings, 1983)
Keywords: Femmes

The Evolution of the Sexual Division of Labour in Teaching: A Nineteenth-Century Ontario and Quebec Case Study - Danylewycz, Marta (Histoire sociale / Social History, 1983)
Number: 31
Keywords: Enseignants; Femmes; Travail

Taking the Veil in Montreal, 1840-1920: An Alternative to Marriage, Motherhood and Spinsterhood - Danylewycz, Marta (Université de Toronto, 1981)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

La majorité oubliée: le rôle des femmes à Montréal au 19e siècle - Cross, D. Suzanne (Les femmes dans la société québécoise, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Canadian City. Essays in Urban History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Neglected Majority: Essays in Canadian Women's History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (Histoire sociale / Social History, 1973)
Number: 12
Keywords: Femmes

The Development of Higher Education for Women at McGill University from 1857 to 1899 with Special Reference to the Role of Sir John William Dawson - Ronish, Donna Ann (Université McGill, 1972)
Keywords: Dawson; William; Femmes; Université McGill